PENGARUH PROGRAM UNIVERSITAS “KEWIRAUSAHAAN”, KREATIVITAS, EFIKASI DIRI WIRAUSAHA TERHADAP NIAT BERWIRAUSAHA - Tantri Yanuar Rahmat Syah; Hery Darmawan; Rojuaniah; Puji Astuti; Kristiana Widiawati (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of entrepreneurial program, creativity, and entrepreneurial self-efficacy on the entrepreneurial intention of Bina Insani University students. Data were collected through an online questionnaire to students who had participated in the entrepreneurial program. Data analysis was conducted using Structural Equation Modeling (SEM) with SPSS and SmartPLS. The results showed that the entrepreneurial program had a positive effect on entrepreneurial intention, while creativity and entrepreneurial self-efficacy had no direct effect on entrepreneurial intention. This research is expected to provide valuable information for educational institutions in their efforts to improve the quality of education and encourage young entrepreneurs from among students.